2019
DOI: 10.7554/elife.47327
|View full text |Cite
|
Sign up to set email alerts
|

FAK activity sustains intrinsic and acquired ovarian cancer resistance to platinum chemotherapy

Abstract: Gene copy number alterations, tumor cell stemness, and the development of platinum chemotherapy resistance contribute to high-grade serous ovarian cancer (HGSOC) recurrence. Stem phenotypes involving Wnt-β-catenin, aldehyde dehydrogenase activities, intrinsic platinum resistance, and tumorsphere formation are here associated with spontaneous gains in Kras, Myc and FAK (KMF) genes in a new aggressive murine model of ovarian cancer. Adhesion-independent FAK signaling sustained KMF and human tumorsphere prolifera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 70 publications
2
67
0
Order By: Relevance
“…Patient survival in both small-cell lung and non-small-cell lung cancers did not correlate with increased levels of nuclear pY397 FAK 24 , suggesting that nuclear pY397 FAK may play different roles in the progression and aggressiveness of different tumor types. Human ovarian cancers also showed increased pY397 FAK in tumor cells compared to stromal cells, and pY397 FAK was widely distributed in both the cytosol and nucleus; 27 however, this study did not investigate the role of nuclear FAK in ovarian cancer or any associations with patient survival. Although these immunohistochemical analyses of human cancers have provided new insights into the prevalence and potential importance of active nuclear FAK within tumor cells, more comprehensive analyses of nuclear FAK localization and activity in various types of tumors are needed to better understand FAK's role in the nucleus of cancer cells.…”
Section: The Roles Of Nuclear Fak In Cancermentioning
confidence: 86%
See 1 more Smart Citation
“…Patient survival in both small-cell lung and non-small-cell lung cancers did not correlate with increased levels of nuclear pY397 FAK 24 , suggesting that nuclear pY397 FAK may play different roles in the progression and aggressiveness of different tumor types. Human ovarian cancers also showed increased pY397 FAK in tumor cells compared to stromal cells, and pY397 FAK was widely distributed in both the cytosol and nucleus; 27 however, this study did not investigate the role of nuclear FAK in ovarian cancer or any associations with patient survival. Although these immunohistochemical analyses of human cancers have provided new insights into the prevalence and potential importance of active nuclear FAK within tumor cells, more comprehensive analyses of nuclear FAK localization and activity in various types of tumors are needed to better understand FAK's role in the nucleus of cancer cells.…”
Section: The Roles Of Nuclear Fak In Cancermentioning
confidence: 86%
“…FAK inhibition was able to overcome paclitaxel resistance by reducing CD44 expression through decreased YB-1 activation and nuclear translocation. Another study found that ovarian cancer with intrinsic or acquired resistance to platinum-based therapies could also be targeted through cotreatment strategies with a FAK inhibitor 27 . Overall, these studies demonstrate that several cancers are able to develop resistance to various therapies and that treating these cancers with mutliple anti-cancer agents including FAK inhibitors could prove useful.…”
Section: Fak Inhibitors In Dual Therapymentioning
confidence: 99%
“…A recent study has shown the use of hyaluronic acid-labeled poly (d,l-lactide-co-glycolide) nanoparticle (HA-PLGA-NP) formulated with paclitaxel and focal adhesion kinase siRNA as an effective delivery system against chemoresistant OC xenograft models [185]. This strategy was designed to target CD44 positive tumour cells abundantly found in ovarian tumours and to knock down focal adhesion kinase, which is upregulated in chemoresistant OC cells [186]. Although this study provided a novel mechanism for focal adhesion kinase knockdown using a siRNA-formulated nanoparticle-based system to tackle chemoresistance in OC, other signaling pathways involved in chemoresistance mechanisms can be explored.…”
Section: Nanoparticle Drug Deliverymentioning
confidence: 99%
“…Examples of such key co-regulators are growth factor receptors and integrin cell adhesion molecules, connecting tumor cells to the extracellular matrix (ECM), and its stiffness in juxtamembrane multiprotein complexes, called focal adhesions [6][7][8]. To date, a variety of focal adhesion proteins (FAP), such as β1 integrin, PINCH1, FHL2, focal adhesion kinase, vimentin and caveolin-1 have been demonstrated to significantly confer tumor resistance to genotoxic agents by modulating the repair of DSB upon radiochemotherapy [9][10][11][12][13][14]. In addition, accumulating evidences suggest that cytoplasmic FAP signaling is linked to nuclear repair dynamics through components of the DNA repair machinery, including DNA-PKcs, ATM, BRCA1, RAD51 and c-Abl [15].…”
Section: Of 18mentioning
confidence: 99%